UPLC-DAD-QToF/MS analysis of green tea phenolic metabolites in their free, esterified, glycosylated, and cell wall-bound forms by ultra-sonication, agitation, and conventional extraction techniques - Das, Protiva Rani; Islam, Md. Tabibul; Lee, Seon-Hye; Lee, Min-Ki; Kim, Jung-Bong; Eun, Jong-Bang (Food science & technology, 2020)
In this study, phenolic metabolites in their free, soluble esterified, and soluble glycosylated forms in green tea infusions and cell wall-bound forms in solid residues obtained by ultrasound treatment, agitation treatment, and normal infusion preparation method were investigated. In total, thirty-three phenolic compounds were characterized including twenty-two flavonoids and eleven phenolic acids using UPLC-DAD-QToF/MS analysis. The flavonoids were sub-characterized as flavanols and flavonols, and phenolic acids were sub-characterized as hydroxybenzoic acid, hydroxybenzoylquinic acid, hydroxycinnamic acid, and hydroxycinnamoylquinic acid. As flavanols, EGCG was dominant in their free form and was significantly higher (p < 0.05) in ultrasound (4094 mg/100 g) and agitation (3906 mg/100 g) treatment than normal infusion (1657 mg/100 g). Kaempferol was predominant flavonols in their free form and was significantly higher (p < 0.05) in ultrasound (54.78 mg/100 g) and agitation (53.87 mg/100 g) treatment than normal infusion (30.67 mg/100 g). In contrary, cell wall-bound phenolics were dominated by gallic acid and were significantly higher (p < 0.05) in normal solid residues (2582 mg/100 g) than agitation (527 mg/100 g) and ultrasound (157 mg/100 g) treatment. This study provides a useful database of different forms of phenolic metabolite profiling of aqueous green tea infusions and solid residues. •Characterize green tea phenolic metabolites using UPLC-DAD-QToF/MS analysis.•Ultrasonic and agitation treatment is best to extract each form of phenolics.•Extraction techniques could increase soluble phenolic yields in green tea infusion.